Hubungan Motivasi Berprestasi dengan Hasil Belajar Bahasa Arab: Studi Kasus Mahasiswi Semester V Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan - Hamdy, Mohammad Zainal (Al-Wazan: Journal of Arabic Education, 2024)
Indicators of motivation are extremely important to the learning and teaching process. Motivation is a basic condition for the learner to achieve major educational goals, whether in the acquisition of knowledge, which is a cognitive aspect for the learner, or in the formation of values and attitudes, which is an emotional aspect in the student’s personality, or in the formation of various skills, which is a sensory-motor aspect. . In this research, the researcher wants to know the extent of the relationship between achievement motivation and academic achievement in the Arabic language at this university, especially among female students at Darul Ulum University Banyuanyar Pamekasan. The researcher uses a quantitative correlational type, which is research that aims to determine whether there is a relationship between two variables or several variables, and from the results of the conclusion that the relationship between these two aspects has a low impact, only 12.3% of all aspects that can affect the Academic achievement of female students. among female students at Darul Ulum University Banyuanyar Pamekasan. With a factor of 0.111 using the Pearson product-moment correlation formula